Infrared study of interactions between the carbon monoxide and support in platinum-supported catalysts - Arteaga, Geomar; Choren, Eduardo; Sánchez, Jorge; Arteaga, Arnedo (Rev. Téc. Fac. Ing. Univ. Zulia)
Interactions between chemisorbed carbon monoxide molecules and surface hydroxyl groups of the support in Pt/ Al2O3 and Pt/SiO2 catalysts were studied by using FTIR spectroscopy. Infrared spectra of the catalysts were measured both before and after the adsorption of CO. Due to the adsorption of CO, the intense 3700-3000 cm-1 band, corresponding to O-H stretching vibration of hydroxyl groups which are involved in hydrogen-bonding, was broadened towards lower frequencies and decreased in its intensity. The 1630 cm-1 band assigned to bending vibration of H-O-H angle decreased in its intensity for the hydrogen saturate catalysts and increased for the catalysts without hydrogen. These changes depend on the amount of adsorbed carbon monoxide. The 3743 cm-1 band, attributed to O-H stretching vibration of isolated silanol groups, was not modifed by chemisorbed CO. The spectral changes observed in the absorption bands of the bonded hydroxyl groups can be explained by a strong interaction through hydrogen bonding between the chemisorbed carbon monoxide and these hydroxyl groups. In the hydrogen-saturated samples, this interaction takes place mainly with the adsorbed water on the support, and in the hydrogen-depleted samples, with the structural hydroxyl groups. The chemisorbed CO molecules that interact with the surface hydroxyl groups vibrates at lower frecuency, causing the assymetry of the CO linear band.